Borehole logging device at Dome F, Antarctica - Naruse, Renji; Shinbori, Kunio; Azuma, Nobuhiko; Saito, Hideharu; Nagatuka, Masaki (1994)
P(論文) A borehole logging device is newly developed for deep drilling to start from 1995 at Dome F, Antarctica. The device is designed to measure the diameter, inclination and azimuth of a hole, ice temperature and fluid pressure. A logging sonde, 2.35m in length and 114mm in diameter, has two sets of stabilizers and a caliper with three contact points. The possible range of measurement is from 130 to 170mm in hole diameter. The data are transmitted by a microprocessor mounted in the sonde to a personal computer at the ice sheet surface. departmental bulletin paper